Water dispersal and functionalization of hydrophobic iron oxide nanoparticles with lipid-modified poly(amidoamine) dendrimers - Boni, Adriano (Langmuir : the ACS journal of surfaces and colloids, 2013)
A novel and facile method for water dispersal of hydrophobic iron oxide nanoparticles based on the amphiphilic PAMAM-C12 dendrimer is described. Stable and highly concentrated water dispersions of multifunctional magnetic nanoparticles were obtained with this single-step approach, and showed interesting relaxometric properties for MRI applications. Importantly, this method does not require substitution of the native hydrophobic capping under nonmild reaction conditions, thus preserving the structural and magnetic properties of the nanoparticles, and extending the possibility of conjugation with thermally labile groups